Screening Early Modern Drama: Beyond Shakespeare - Aebischer, Pascale (Cambridge University Press, 2013)
While film adaptations of Shakespeare's plays captured the popular imagination at the turn of the last century, independent filmmakers began to adapt the plays of Shakespeare's contemporaries. The roots of their films in European avant-garde cinema and the plays' politically subversive, sexually transgressive and violent subject matter challenge Shakespeare's cultural dominance and the conventions of mainstream cinema. In Screening Early Modern Drama, Pascale Aebischer shows how director Derek Jarman constructed an alternative, dissident, approach to filming literary heritage in his 'queer' Caravaggio and Edward II, providing models for subsequent filmmakers such as Mike Figgis, Peter Greenaway, Alex Cox and Sarah Harding. Aebischer explains how the advent of digital video has led to an explosion in low-budget screen versions of early modern drama. The only comprehensive analysis of early modern drama on screen to date, this groundbreaking study also includes an extensive annotated filmography listing forty-eight surviving adaptations.